The Paddy and Rice Quality of Three Varieties of Indonesian Local Aromatic Paddy. (September 2019) - Purwaningsih; Indrasari, S D
Abstract: The purpose of this research was to study the physical, milling, nutrition quality and physichochemical characteristic of three Indonesian local aromatic paddy namely Kewal Balik Semah, Cere Mas, and Segara Anak. The research materials were obtained from local farmers in Lebak, Banten Province, and Sukamandi, West Java Province. The analysis was conducted at the Rice Quality Laboratory at Indonesian Center for Rice Research (ICRR), Sukamandi. The data were analysed using Analysis of Variance (ANOVA) and followed by Duncan's Multiple Range Test (DMRT) if differences were found. The results indicated that paddy rice moisture content varied 11.5-13.4%, empty grain 2.0-9.4%, paddy density varied 339-568 g/l, 1000 grain weight range from 20.5-29.4 g, chalky + immature grain 0.2-0.7%, and yellow + damaged grain 0.7-5.3%, paddy length 5.2-6.04 mm (short to medium) and paddy L/B ratio ranged 2.04-2.41 (medium). Milling percentage ranged 62.5-71.5%, head rice percentage varied 56.7-85.4%, broken rice percentage ranged 14.5-41.0% and brewer 0.1-2.4%. Chalky grain <1% and damaged grain varied 0.07-0.4%. Milled rice whiteness ranged from 43.6-55.8%, and translucensy 0.5-2.8%. The amylose content of three varieties are categorised as medium amylose. Gel consistency characters is soft texture and gel temperature are high to high intermediate (1-3). Among of the cultivars the protein content ranged 7.4-8.2%.